A quality adjusted measure of labour services for Ireland - Keeney, Mary J. (Economic & Social Studies, 2010)
This paper presents annual indices of labour input adjusted for the age, education and gender distributions of the Irish workforce for the period 1999-2008. Growth in labour services is divided between the increase in hours and improvement in the productive quality of these hours. Improvement in labour quality, as proxied by education, age and gender, has added on average 0.7 percentage points per year to the growth rate in total labour input. Changes in education account for two-thirds of the improvement in labour quality, with gender and age distributions equally sharing the remaining third. Even in the face of declining total employment, growth in labour services remained positive in 2008 due to past investment in human capital. A key application of this quality-adjusted labour series is that a proportion of growth usually attributed to total factor productivity growth can now be accounted for as an improvement in the quality of labour input.
Keywords: Labour productivity; Human capital; Ireland